Hubungan Hubungan Literasi Digital dengan Prestasi Akademik Mahasiswa Program Studi Pendidikan IPS di Universitas Tanjungpura Pontianak - Haliza, Nur; Aminuyati, Aminuyati; Karolina, Venny; Achmadi, Achmadi; Rahmatika, Ika (Peneliti.net, 2024)
Digital Literacy is one of the crucial components in the field of education, particulary in higher education institutions throughtout Indonesia. This study aims to assess the level of digital literacy among students, their academic achievements, and the correlation between digital literacy and academic performance of Social Studies Education students at Tanjungpura University, Pontianak. This research adopts a quantitative approach, utilizing a survey method with a questionnaire as the data collection tool distributed to students as research subjects. The findings of the study indicate that: 1) the level of digital literacy among students is relatively high (60,8%), 2) student’s academic performance is notably high (80,4%), and 3) there exists a weak iverse correlation between digital literacy anda academic performance (r=-0,048), with a p-value of 0,633 (p>0,05),signifying a negligible relationship between the variables. Consequently, this research concludes that while digital literacy is important, it is not a sole determinant of high academic ahievement among students. Numerous other factors, both internal and external to the individual, contribute to students’ academic success.